1998
DOI: 10.1177/03635465980260061201
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Effect of Monopolar Radiofrequency Energy on the Properties of Joint Capsule

Abstract: The purpose of this in vivo study was to analyze the short-term tissue response of joint capsule to monopolar radiofrequency energy and to compare the effects of five power settings at 65 degrees C on heat distribution in joint capsule. In 12 mature Hampshire sheep, the medial and lateral aspects of both stifles were treated with monopolar radiofrequency energy under arthroscopic control in a single uniform pass to the synovial surface. The radiofrequency generator power settings were 0, 10, 15, 20, 25, and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
91
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(97 citation statements)
references
References 27 publications
3
91
0
3
Order By: Relevance
“…This was followed by a gradual improvement of the tissue's mechanical properties by 6 weeks postoperatively and a full return of preoperative stiffness at 12 weeks. Similarly, Hecht et al 10 reported a 65% reduction of tissue stiffness at 2 weeks following surgery, and a 20% reduction at 6 weeks postoperatively, with a return to preoperative tissue stiffness at 12 weeks following thermal application in a study using a bovine model. Therefore, passive range of motion is initially performed without stretching, as it is necessary to carefully progress the range of motion during the first 4 to 6 weeks when collagen tissue may be susceptible to stretch-out due to a decrease in tissue stiffness.…”
Section: Discussionmentioning
confidence: 84%
“…This was followed by a gradual improvement of the tissue's mechanical properties by 6 weeks postoperatively and a full return of preoperative stiffness at 12 weeks. Similarly, Hecht et al 10 reported a 65% reduction of tissue stiffness at 2 weeks following surgery, and a 20% reduction at 6 weeks postoperatively, with a return to preoperative tissue stiffness at 12 weeks following thermal application in a study using a bovine model. Therefore, passive range of motion is initially performed without stretching, as it is necessary to carefully progress the range of motion during the first 4 to 6 weeks when collagen tissue may be susceptible to stretch-out due to a decrease in tissue stiffness.…”
Section: Discussionmentioning
confidence: 84%
“…During the second half of our experiment, the expansion of the papillary dermis was due mainly to an increase in intercellular substance and the resident cell population (fibroblasts and histiocytes). In other studies, treatment with radiofrequency has been shown to activate tissue repair, causing the proliferation of fibroblasts, among other regenerative processes [26,27]. In no case did we observe any inflammatory response, unlike Zelickson et al [17] and Shumaker et al [19] who have done for human skin from the abdomen and the skin of pigs with cosmetic implants treated with radiofrequency, respectively.…”
Section: Discussionmentioning
confidence: 51%
“…In a rabbit model, Schaefer et al (1997) described a generalized fibroblastic response characterized by a marked increase in cellularity and vascularity 8 weeks postoperatively. Hecht et al (1998) examined monopolar radiofrequency energy effects in a sheep model with postoperative follow-up times of 0, 2, 6 and 12 weeks and found immediate postoperative collagen hyalinization and cell necrosis followed by an active tissue repair beyond the sixth week. Hayashi et al (1999) performed a histological evaluation of the glenohumeral joint capsule after laser-assisted shrinkage in 42 patients with shoulder instability.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, progressive rehabilitation causes increased fibroblast proliferation and collagen synthesis in various animal models of tendon and ligament healing, but intensive proliferation and hypercellularity seem to have adverse effects on the mechanical properties of healing tissue (Woo et al 1982, Frank et al 1991, Kamps et al 1994, Atkinson et al 1999). These results have generated controversy concerning the role of mechanical loading, especially since cell necrosis and subsequent intensive fibroblastic response after RF shrinkage have been reported (Hayashi et al 1999, Hecht et al 1998, Pullin et al 1997, Schaefer et al 1997.…”
mentioning
confidence: 99%